Pengaruh Komunikasi Intern Terhadap Efektivitas Kerja Pegawai di Perguruan Tinggi Kota Palembang, Indonesia - Rusmaini Rusmaini (El-Idare, 2019)
Work effectiveness is the degree of accuracy of the organization in achieving the objectives seen from the activities carried out. Many factors that influence work success, such as internal communication, office layout, work motivation and others. This article will discuss the influence of internal communication on improving work. The purpose of this article is to understand the presence or absence of internal communication and most internal communication is related to cooperation both simultaneously and partially. The population to collect article data is employees at universities in Palembang-Indonesia City. The total population is 90 people with the data collection method used is a questionnaire and documentation. Obtained data obtained were analyzed using descriptive contributions and multiple linear regression analysis using SPSS for windows release 16. Based on the descriptive analysis obtained by the level of internal communication of 86% including the excellent category, while the level of work requirements amounted to 78.78% including the good category. Based on the calculation of multiple linear regression analysis also obtained Fcount of 17,234 with a significance of 0,000. Conclusion that the working hypothesis (Ha) is accepted, that is there is internal communication motivation towards work effectiveness. The amount is 28.4% while it is partial 16% for leadership variables and 5.29% for internal communication.